Risk of hypothermia in elderly patients with diabetes. - Neil, H; Dawson, J; Baker, J (1986)
The incidence of admissions of patients with hypothermia was determined to examine whether hypothermia was more common in elderly patients with diabetes than in the general population after diabetic metabolic emergency cases had been excluded. A prospective survey of three accident and emergency departments identified 134 cases of hypothermia admitted from a catchment population of almost 157,000 aged 65 or over during the winters of 1981-2 to 1983-4. The predicted number of patients with diabetes in the population was nearly 5600 (3.5%). Twenty three admissions for hypothermia (17%) occurred in 20 patients with previously diagnosed diabetes. Women made up 87% of the diabetic admissions; the ratio of diabetic to non-diabetic admission rates in women was 7.9 (95% confidence interval 5.3 to 12.0). After excluding diabetic metabolic emergency admissions the ratio was 6.4. The ratio in men was 2.4, but the small number of admissions produced wide confidence intervals. Ten of the admissions with diabetes (43%) had pathological disorders that are associated with an increased risk of hypothermia. The frequency of these conditions is higher in patients with diabetes than in the general population and partly explains the increased risk of hypothermia in these patients.